Unexpected premalignant gynecological lesions in women undergoing vaginal hysterectomy for utero-vaginal prolapse - Elbiaa, Assem A.M.; Abdelazim, Ibrahim A.; Farghali, Mohamed M.; Hussain, M.; Omu, A.E. (Menopause Review/Przegląd Menopauzalny, 2015)
Aim of the study was to estimate the incidence of unexpected premalignant gynecological lesions in women undergoing vaginal hysterectomy for utero-vaginal prolapse. Material and methods : Eighty women with asymptomatic utero-vaginal prolapse were included in this prospective study for vaginal hysterectomy after preoperative preparation and after written informed consent. Women included in this study were screened preoperatively by high vaginal swab, Pap smear, endometrial biopsy and trans-vaginal ultrasound. Surgically removed uteri and ovaries were sent for histopathological examination. Results of histopathological examination as gold standard were compared with conventional gynecological screening methods. Results : Histopathological examination of surgically removed uteri and ovaries after vaginal hysterectomy for uterovaginal prolapse showed abnormal findings in 61.25% (49/80) of studied cases (10 chronic cervicitis; 20 cervical intra-epithelial neoplasia-1 [CIN-1]; 5 CIN-2; 2 CIN-3; 10 simple endometrial hyperplasia without atypia and 2 simple serous ovarian cyst). Also, histopathological examination showed premalignant changes in 33.75% (27/80) of studied cases (20 CIN-1; 5 CIN-2 and 2 CIN-3), which mean 50% sensitivity of pre-operative Pap smear to detect premalignant cervical changes. Conclusions : Asymptomatic women with utero-vaginal prolapse may have associated premalignant lesions which may not be detected by conventional screening methods, and this should be explained preoperatively for women undergoing surgery, especially if conservative management was considered.